Faktor yang Memengaruhi Tingkat Pemahaman Akuntansi Mahasiswa Program Studi Akuntansi pada Perguruan Tinggi Swasta (PTS) di Jember - Melinda Anggreyni; Suwignyo Widagdo; Nurshadrina Kartika Sari (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2022)
This study aims to analyze the effect of Intellectual Intelligence (IQ), Emotional Intelligence (EQ), Spiritual Intelligence (SQ), Learning Behavior and Learning Interest on the Level of Accounting Understanding partially or simultaneously. This study took a population of 320 students majoring in Accounting, Faculty of Economics at Muhammadiyah University of Jember and STIE Mandala Jember in 2020. The research sample was 71 students of STIE Mandala Jember and 249 students of Muhammadiyah University of Jember. Samples were taken using purposive sampling method. The data collection method used in this study is the survey method through a questionnaire. The statistical method for hypothesis testing uses multiple linear regression analysis. The results showed that partially Spiritual Intelligence (SQ) and Learning Interest had a significant effect on the level of accounting understanding, while Intellectual Intelligence (IQ), Emotional Intelligence (EQ) and Learning Behavior had no significant effect on the level of accounting understanding. Simultaneously all independent variables, namely Intellectual Intelligence (IQ), Emotional Intelligence (EQ), Spiritual Intelligence (SQ), Learning Behavior and Interest in Learning have a significant effect on the level of accounting understanding.